Dissolution of marriage upon conversion of religion: looking at the marriage and divorce settlement / Malia Afzan Ismail, Norasyikin Ahmad, Sabariah Mohd Ismail - Ismail, Malia Afzan; Ahmad, Norasyikin; Mohd Ismail, Sabariah (2006)
This thesis concerns with the family law in Malaysia where it deals with the area of divorce settlement upon conversion into Islam. The main intention of this research is to make a fair comparison which court has jurisdiction to grant a divorce and which family law could be applied for granting the divorce settlement to both parties. The position of our judiciary is split into two jurisdictions whereby each of the court is bound to the converted party whilst the other party is bound to High Court's jurisdiction only. The amendment of Article 121 (1A) has split both jurisdiction where neither of it can contravened each other's jurisdiction. Furthermore, comparison is made between the Law Reform (Marriage and Divorce) Act 1976 and the Islamic Family Law (Federal Territories) Act 1984 in order to understand the rights of both converted party and the non-converted party. Besides that this research also put a vital concentration on relevant decided cases before and after the amendment of Article 121 (1A) in order to determine factors taken by the court in deciding the divorce settlement. There are two forms used as research methodology which the vital methodology is cases review as it is the major part to understand the position of the court on the issues of granting a divorce together with settlements to the parties. Library research is the second methodology used in this research which consists of case laws, textbooks, articles, and statutes.